Considerations for an Inclusive Global Theological Education - Mombo, Esther (The Ecumenical Review, 2019)
This article considers the role of theological education in developing the ministry of the church and the need for it to be relevant to the realities and needs of the people it is to serve. The article considers three factors – racism, imperialism, and tribalism – that influence theological education in different ways. It then turns to a consideration of African-American womanist theology and African women's theology – as reflected in the Circle of Concerned African Women Theologians – and the similarities between these two approaches as expressions of liberation theology and their relevance for inclusive global theological education.
paid
Keywords: imperialism; racism; the Circle of Concerned African Women Theologians; theological education; tribalism; womanist theology